KONTEKSTUALITAS KORUPSI DALAM ALQURAN - Muhamad Rezi; Sefri Auliya (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2019)
One of the most complex problems for the Indonesian people today is corruption. Seeing the phenomenons of corruptions, the author considers the need to look back in full at the Qoran, especially in the verses that are conditional with the message of anti-corruption so that it is expected that there is a comprehensive and clear picture that Islam always appears in a strong position as a force to eradicate corruption. The main problem or problem, namely: How is the interpretation of the Qur'anic verses that speak related to the problem of corruption in the present context and how to eradicate it. There is no direct text that talks about the specifications of corruption and other similar dirty practices. In the Quran, corruption is understood through the word ghalla or ghulul, which means the misappropriation of spoils of war in the letter Ali Imran verse 161, besides that it can also be understood through statements about the prohibition of consuming the property of others in an illegal way, in a contemporary context, both verses understood as an argument about corruption.